2014
DOI: 10.1161/circgenetics.114.000676
|View full text |Cite
|
Sign up to set email alerts
|

Shared Molecular Pathways and Gene Networks for Cardiovascular Disease and Type 2 Diabetes Mellitus in Women Across Diverse Ethnicities

Abstract: It has long been known that cardiovascular disease (CVD) and type 2 diabetes mellitus (T2D) share many common risk factors and pathophysiological intermediaries including obesity, dyslipidemia, insulin resistance, and proinflammatory and prothrombotic states. [1][2][3] However, the key molecular drivers underlying these highly correlated phenotypes as well as the potential regulatory networks shared in the pathogenesis of CVD and T2D remain poorly understood. Clinical Perspective on p 919Of the ≈60 genetic lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 56 publications
8
50
0
Order By: Relevance
“…Leaky vessels and endothelial damage would permit insulin diffusion into the interstitial space, leading to suboptimal insulin delivery to distal tissues. These results are the first direct evidence for the recently proposed role for CD93 in T2D (12). …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Leaky vessels and endothelial damage would permit insulin diffusion into the interstitial space, leading to suboptimal insulin delivery to distal tissues. These results are the first direct evidence for the recently proposed role for CD93 in T2D (12). …”
Section: Discussionsupporting
confidence: 74%
“…More recently, the CD93 gene has been identified as a potential regulator of pathways common to both T2D and CVD (12). Interestingly, CD93 expression is upregulated by conditions relevant to diabetes or its complications, for example, flow-related shear stress (13) due to endothelial dysfunction; during the development of new but leaky blood vessels (14), as observed in retinopathy; and during ischemia-related inflammation of cerebral vascular endothelium (15), thus reflecting myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in a series of recent publications [16, 65] in developing new findings and approaches, user-friendly and publicly accessible web-servers will significantly enhance their impacts [20], we shall make efforts in our future work to provide a web-server to displaying findings that can be manipulated by users according to their need.…”
Section: Discussionmentioning
confidence: 99%
“…For example, disease genes and drug targets of coronary heart disease (CAD) and T2D could be identified effectively by systems biology approaches [18, 19]. Chan KH et al identified key drivers that included COL1A1, COL3A1, and ELN in the shared pathways for both CAD and T2D based on the protein-protein interaction network (PPIN) and genome-wide association studies [20]. In addition, the highly central importance proteins in core networks or sub-networks are globally or locally important nodes which could act as functional modules or pathways or key role genes to uncover the pathogenesis and therapeutic ways of disease [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation